2010
DOI: 10.1002/bjs.7082
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of polyvinylidene fluoride-coated polypropylene mesh used for laparoscopic intraperitoneal onlay repair of incisional hernia

Abstract: Laparoscopic intraperitoneal onlay DynaMesh repair was associated with a high rate of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 34 publications
0
25
0
1
Order By: Relevance
“…In a small series of patients, DynaMesh ® -IPOM was associated with a high incidence of bowel obstruction caused by adhesion of the whole surface of the mesh to the bowel, with histologically proven severe foreign body reaction in the bowel. 9 Various experimental models and studies suggest decreased adhesion formation with the use of the Parietex™ Composite mesh, [10][11][12][13][14] with most suggesting that coated meshes perform better, with less adhesion formation. The guidelines for laparoscopic treatment of ventral and incisional abdominal wall hernias suggest that more research is needed to understand the mesh requirement for individual groups of patients who react differently to different types of mesh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a small series of patients, DynaMesh ® -IPOM was associated with a high incidence of bowel obstruction caused by adhesion of the whole surface of the mesh to the bowel, with histologically proven severe foreign body reaction in the bowel. 9 Various experimental models and studies suggest decreased adhesion formation with the use of the Parietex™ Composite mesh, [10][11][12][13][14] with most suggesting that coated meshes perform better, with less adhesion formation. The guidelines for laparoscopic treatment of ventral and incisional abdominal wall hernias suggest that more research is needed to understand the mesh requirement for individual groups of patients who react differently to different types of mesh.…”
Section: Discussionmentioning
confidence: 99%
“…Coated meshes, which are commonly used in intraperitoneal mesh repairs, are typically associated with seroma formation because of the resulting impaired drainage of fluid due to the barrier coating. 9 There may be other contributing factors, such as the number and size of the defects, difficulty of dissection, mesh fixation technique and operation time. 15 The optimal mesh type for LIVHR has yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…The mesh used in our series (Dyna Mesh) was developed specifically to minimise the risk of adhesion formation. Despite promising results reported by Berger et al in 2009 after using this mesh in 344 cases [12], there was recent criticism from a small series (29 patients) that reported 17.24% re-operation rate due to adhesions (5 cases) and explantation of 3 meshes [1]. The importance of the latest paper is that it describes adhesion forming through the pores of the mesh rather than to the mesh itself.…”
Section: Discussionmentioning
confidence: 98%
“…Its use had been backed by safe data together with a large series of 344 patients [12] with no long term complications and even the cases of early infection were treated conservatively without removing the mesh. However; a recent study has questioned the safety of this mesh [1]. Fortelny et al reported a series of 29 cases with an alarmingly high incidence of re-operation after PVF-PP insertion (20%).…”
Section: Journal Of Gastrointestinal and Digestive Systemmentioning
confidence: 99%
See 1 more Smart Citation